Multifunctional Graphene Oxide‐based Triple Stimuli‐Responsive Nanotheranostics. (1st April 2014) - Chen, Yu; Xu, Pengfei; Shu, Zhu; Wu, Meiying; Wang, Lianzhou; Zhang, Shengjian; Zheng, Yuanyi; Chen, Hangrong; Wang, Jin; Li, Yaping; Shi, Jianlin
<x xml:space="preserve">Abstract</x> Construction of multifunctional stimuli‐responsive nanosystems intelligently responsive to inner physiological and/or external irradiations based on nanobiotechnology can enable the on‐demand drug release and improved diagnostic imaging to mitigate the side‐effects of anticancer drugs and enhance the diagnostic/therapeutic outcome simultaneously. Here, a triple‐functional stimuli‐responsive nanosystem based on the co‐integration of superparamagnetic Fe3O4 and paramagnetic MnOx nanoparticles (NPs) onto exfoliated graphene oxide (GO) nanosheets by a novel and efficient double redox strategy (DRS) is reported. Aromatic anticancer drug molecules can interact with GO nanosheets through supramolecular π stacking to achieve high drug loading capacity and pH‐responsive drug releasing performance. The integrated MnOx NPs can disintegrate in mild acidic and reduction environment to realize the highly efficient pH‐responsive and reduction‐triggered T1‐weighted magnetic resonance imaging (MRI). Superparamagnetic Fe3O4 NPs can not only function as the T2‐weighted contrast agents for MRI, but also response to the external magnetic field for magnetic hyperthermia against cancer. Importantly, the constructed biocompatible GO‐based nanoplatform can inhibit the metastasis of cancer cells by downregulating the expression of metastasis‐related proteins, and anticancer drug‐loaded carrier can significantly reverse the multidrug resistance (MDR) of cancer cells.